Contrabandistas de seda y plata: puertos centroamericanos en las rutas transpacíficas (1585-1605) - Rafael Obando Andrade (Nuevo mundo - Mundos Nuevos, 2019)
Beyond being "the Limits of Empire" in the Audience of the Confines, the Kingdom of Guatemala played a key role in the transoceanic shipping routes that connected the various regions of the world during the colonial era. Especially important were the ports of Acajutla and El Realejo on the Callao-Acapulco-Manila route. In this context, the royal prohibitions of voyages from Callao fostered an emerging smuggling trade in which the main goods were silver and silk. The original research presented here reveals Central American participation in the diversion of part of the silver intended in principle for Seville to China, where it reached a higher value than gold, and thus endangered the Atlantic economy.